2016
DOI: 10.1007/s11104-016-2823-3
|View full text |Cite
|
Sign up to set email alerts
|

Root-emitted volatile organic compounds: can they mediate belowground plant-plant interactions?

Abstract: Background Aboveground, plants release volatile organic compounds (VOCs) that act as chemical signals between neighbouring plants. It is now well documented that VOCs emitted by the roots in the plant rhizosphere also play important ecological roles in the soil ecosystem, notably in plant defence because they are involved in interactions between plants, phytophagous pests and organisms of the third trophic level. The roles played by root-emitted VOCs in between-and withinplant signalling, however, are still po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 213 publications
(320 reference statements)
2
123
0
2
Order By: Relevance
“…Terpenoids are also involved in the plant-plant interaction, repelling pests and attracting enemies of pests (Unsicker et al 2009). Volatile terpenoids are involved especially in attracting pollinators, seed dispersal, defense against herbivores from both below-and above-ground (Ali et al 2012;Delory et al 2016), plant-plant signaling and protection against pathogens (Huang et al 2012) (Fig. 2).…”
Section: Multifunctionality Of Volatile Terpenoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Terpenoids are also involved in the plant-plant interaction, repelling pests and attracting enemies of pests (Unsicker et al 2009). Volatile terpenoids are involved especially in attracting pollinators, seed dispersal, defense against herbivores from both below-and above-ground (Ali et al 2012;Delory et al 2016), plant-plant signaling and protection against pathogens (Huang et al 2012) (Fig. 2).…”
Section: Multifunctionality Of Volatile Terpenoidsmentioning
confidence: 99%
“…Arabidopsis has been shown to emit two terpenoids, (3,S)-(E)-nerolidol and its derivative (E)-4,8-dimethyl-1,3,7-nonatriene, when the strawberry nerolidol synthase gene was introduced into the plants, resulting in greater attraction of the predators of predatory mites (Kappers et al 2005). Caryophyllene, emitted from the roots of Maize plants, is known to be an herbivore-induced below-ground signal, which strongly attracts entomopathogenic nematodes (Rasmann et al 2005;Delory et al 2016). Similarly, Ozawa et al (2000) demonstrated that (Lotus japonicus) shoots infested with spider mites released a blend of volatiles that attracted predators of mites (Phytoseiulus persimilis).…”
Section: Terpenoid Volatiles: An Immediate Response In Plant Defensementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the uptake from the atmosphere, the very fast mineralization rates are likely important in shaping the net 340 BVOC emissions from soil. The net BVOC release from soil to the atmosphere in general is low compared to the plant emissions (Peñuelas et al, 2014), but emissions may represent a minor portion of the amount that was excreted by soil microbes (Insam and Seewald, 2010;Garbeva et al, 2014) or by roots (Lin et al, 2007;Delory et al, 2016), produced for example with the purpose of communication. It is thus possible that BVOCs are a significant source of carbon to soil microbes and hence that BVOC formation and degradation may be an important but little recognized part of internal 345 carbon cycling in soil.…”
Section: Page 12mentioning
confidence: 99%